Triterpenoid Biosynthesis and Engineering in Plants - Sawai, Satoru; Saito, Kazuki (Frontiers in Plant Science, 2011)
Triterpenoid saponins are a diverse group of natural products in plants and are considered defensive compounds against pathogenic microbes and herbivores. Because of their various beneficial properties for humans, saponins are used in wide-ranging applications in addition to medicinally. Saponin biosynthesis involves three key enzymes: oxidosqualene cyclases, which construct the basic triterpenoid skeletons; cytochrome P450 monooxygenases, which mediate oxidations; and uridine diphosphate-dependent glycosyltransferases, which catalyze glycosylations. The discovery of genes committed to saponin biosynthesis is important for the stable supply and biotechnological application of these compounds. Here, we review the identified genes involved in triterpenoid biosynthesis, summarize the recent advances in the biotechnological production of useful plant terpenoids, and discuss the bioengineering of plant triterpenoids.